The influence of nutrient concentration and hydroponic growing media on the growth and yield of pagoda mustard greens (Brassica narinosa L.) - Fauzi , Deni Ahmad; Isnaeni, Selvy; Nurhidayah, Siti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
Production of pagoda mustard greens is currently still limited, while market demand is increasing. For this reason, it is necessary to increase the yield of pagoda mustard plants through hydroponic with optimization of nutrition and media. This study aimed to determine the plant responses to the application of AB Mix nutrient concentration and growing media types, as well as the effects of their interaction on the growth and yield of pagoda mustard greens. The research was conducted in June-July 2022 at a Screen House in Ciwidey, Bandung, at an altitude of 1,200 meters above sea level. The research used a factorial completely randomized design (CRD) with three replications. The first factor was the concentration of AB Mix nutrients 1,050; 1,150; and 1,250 ppm, and the second factor was the growing media rockwool, cocopeat, sponge, and rice husk charcoal. Data were analyzed using ANOVA and further tested using the Least Significant Difference (LSD) at the 5% level. The results showed that AB Mix nutrient with a concentration of 1,250 ppm or rockwool planting media was able to increase the growth and yield of pagoda mustard greens, but there was no interaction between the two treatment factors. Keywords: AB Mix nutrients; cocopeat; rice husk charcoal; rockwool; sponge